Sustainability-Oriented Transformation in Archipelagic Maritime Transport Management Systems - Okol Sri Suharyo; Ayip Rivai Prabowo; Eko Krisdiono (Penerbit Goodwood, 2026)
Purpose: This study investigates sustainability-oriented transformation in archipelagic maritime transport systems by integrating technological innovation, environmental performance, and governance effectiveness into a unified framework. Methodology: This study employed a mixed-method approach that integrated bibliometric analysis, stakeholder survey analysis using Structural Equation Modelling (SEM), and system dynamics interpretation. The bibliometric dataset comprised 1,245 publications retrieved from the Scopus and Web of Science databases, and survey data were collected from 320 maritime stakeholders across Indonesia, the Philippines, and Japan. Results: The findings indicate that technological innovation significantly enhances environmental performance, and governance effectiveness strengthens maritime resilience. Environmental performance also serves as a mediating mechanism that links innovation and resilience. Furthermore, the simulation results demonstrate that integrated green investment and digitalization policies can substantially reduce maritime emissions and improve long-term system resilience. Conclusion: Sustainability transformation in archipelagic maritime systems requires simultaneous advancements in digital innovation, environmental governance, and institutional coordination. Limitations: This study is limited by its regional focus on Southeast Asian archipelagic systems and the use of cross-sectional survey data. Contribution: This research contributes an integrative sustainability framework that supports maritime policy development for resilient, low-carbon, and digitally connected maritime transport systems.